ANALISIS KELAYAKAN INDUSTRI KECIL ROTI DAN KUE DI KECAMATAN TAMPAN KOTA PEKANBARU - Albab, Iqbal Al; Jahrizal, Jahrizal; Pailis, Eka Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to analyze the feasibility of small industries of Roti and Kue in Kec Tampan Pekanbaru City. The population in this research is baking and cake industry in Kecamatan Tampan Kota Pekanbaru yaiti as many as 20 industries. In this study the entire population was studied using the census method. The type of data used in this study are primary data and secondary data. Methods of data collection with interviews, questionnaires, and observations. Data analysis used in this research is descriptive analysis and quantitative analysis. The industry feasibility analysis using Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate Return (IRR). From the research that has been done by the writer, can know the average income of Bread and cake businessman of Rp 266,307,917 per year. . With benefit Cost Ratio of 1.15% and Internal Rate of Return of 12.66% so that the business is feasible to be developed.Keywords : feasibility analysis, B / C and Internal Rate of Return